(untitled) (Journal of Academic Research, 2026)
Green synthesis of gold nanoparticles (AuNPs) has gained popularity as an economical and eco-friendly substitute for traditional chemical processes. Papaya leaf extract was used in this work as a natural reducing and stabilizing agent to create gold nanoparticles. When papaya leaf aqueous extract and chloroauric acid solution were combined under moderate reaction conditions, the synthesis of AuNPs was verified by a noticeable color shift. X-Ray Diffraction (XRD), ultraviolet–visible (UV–Vis) spectroscopy and Fourier transform infrared spectroscopy (FTIR) were used to analyze the produced gold nanoparticles. A distinctive surface plasmon resonance (SPR) absorption band at 520–550 nm was found by UV–Vis examination, demonstrating the stability and successful production of gold nanoparticles. The XRD patterns showed the strong crystallinity of the biosynthesized nanoparticles and verified the face-centered cubic (FCC) structure of gold, FTIR analysis confirmed the presence of phytochemicals from Carica papaya leaf extract as capping agents. The findings show that papaya leaf extract works well as a green agent for producing gold nanoparticles without the usage of hazardous substances.